Solid-Phase Microextraction and Related Techniques in Bioanalysis - Hiroyuki Kataoka (Molecules, 2023)
Living organisms, such as microorganisms, plants and animals, are composed of complex constituents, which may include bioactive components that maintain their functions [...]